Development and study of innovative deep water piled structures of high bearing capacity - Doubrovsky, Michael; Gerashchenko, Andrey; Dobrov, Igor; Dubrovska, Olga (Основи і фундаменти, 2019)
Deep water piled clusters and structures supported by large mono-piles are designed to take up significant lateral and pressing loads. In particular it relates to offshore structures which foundations need long piled supports of high bearing capacity. Two innovative structures and technologies have been worked out to optimize stress-strain state of piled clusters and mooring/fender dolphins. (1) Developed is effective and less resource-demanding design when connection of all pipe piles with large diameter steel casing provides their joint work and favorable distribution of stresses and deformations in pile cluster. (2) To increase energy-absorbing capacity of mooring/fender dolphins it is worked out and researched a new design of combined tubular mono-pile structure. It incorporates internal flexible pile and damping element (cushion) placed between external and internal piles’ heads. For both innovative and patented solutions laboratory tests and numerical modeling were fulfilled and compared. Study of peculiarities of two innovative structural and technological solutions of piled cluster and mooring/fender dolphin on combined mono-pile was fulfilled by testing on physical models in laboratory conditions and by numerical modeling (FEM). The preliminary stage of tests (experiments without soil with fixed piles’ tips) occurred to be useful for study of structural behavior of both new designs [3, 4]. The main stage of experiments in the sand box with models of both proposed improved structures and their corresponding numerical modeling gave interesting results due to consideration of structure-soil interaction. It also confirmed proper selection of the appropriate calculation program (by comparison of measured and calculated data). Obtained results demonstrated advantages of proposed solutions and explained peculiarities of their innovative structures.